Association of Modified Systemic Lupus Erythematosus Responder Index Attainment With Long‐Term Clinical Outcomes: A Five‐Year Prospective Study. Issue 3 (16th December 2022) - Connelly, Kathryn; Kandane‐Rathnayake, Rangi; Hoi, Alberta; Louthrenoo, Worawit; Hamijoyo, Laniyati; Luo, Shue Fen; Wu, Yeong‐Jian Jan; Cho, Jiacai; Lateef, Aisha; Lau, CS; Chen, Yi‐Hsing; Navarra, Sandra; et al.
Abstract : Objective: In trials of systemic lupus erythematosus (SLE), the SLE Responder Index (SRI) is the most commonly used primary efficacy end point but has limited validation against long‐term outcomes. We aimed to investigate associations of attainment of a modified version of the SRI (mSRI) with key clinical outcomes in SLE patients with up to 5 years of follow‐up. Methods: We used data from a large multicenter, longitudinal SLE cohort in which patients received standard of care. The first visit with active disease (defined as SLE Disease Activity Index 2000 [SLEDAI‐2K] score ≥6) was designated as baseline, and mSRI attainment (defined as a reduction in SLEDAI‐2K ≥4 points with no worsening in physician global assessment ≥0.3 points) was determined at annual intervals from baseline up to 5 years. Associations between mSRI attainment and outcomes including disease activity, glucocorticoid dose, flare, damage accrual, Lupus Low Disease Activity State (LLDAS), and remission were studied. Results: We included 2, 060 patients, with a median baseline SLEDAI‐2K score of 8. An mSRI response was attained by 56% of patients at 1 year, with similar responder rates seen at subsequent annual time points. Compared to nonresponders, mSRI responders had significantly lower disease activity and prednisolone dose and higher proportions of LLDAS and remission attainment at each year, and less damage accrual at years 2 and 3. Furthermore, mSRI responder status at 1 year predicted clinical benefit at subsequent years across most outcomes, including damage accrual (odds ratio [OR] range 0.58–0.69, P < 0.05 for damage accrual ORs at all time points). Conclusion: In SLE patients with active disease receiving standard of care, mSRI attainment predicts favorable outcomes over long‐term follow‐up, supporting the clinical meaningfulness of SRI attainment as an SLE trial end point.